Maternal and foetal outcome of eclampsia in a referral hospital - Ghosh, Mousumi Das; Singh, Vinita; Ray, Alokananda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Eclampsia is a life-threatening condition, common in developing countries with high fatality rate. It is a cause of maternal and foetal mortality and morbidity. The aim of the study is to determine the maternal and foetal outcome in Tata Main Hospital, Jamshedpur, Jharkhand, India. Methods: All cases of eclampsia were analysed from January 2012 to December 2014 from admission to discharge or death of the patient. Age, parity, antenatal care, interval between attack and admission, blood pressure on admission, gestational age and mode of delivery were taken into account. There were 135 cases of eclampsia out of 14572 deliveries. Only singleton pregnancies were analysed. Results: The incidence of antepartum eclampsia was 84.4%, intrapartum 3% and postpartum 12.5 %. 83% patients were primigravida, 33% less than 20 yrs,42% had no antenatal checkup and 45% had < 4 visits. Only 15% patients received magnesium sulphate before referral to the hospital. There were four maternal deaths and twenty-one perinatal deaths. Eleven patients needed ventilatory support, four developed pulmonary oedema, two patients had respiratory depression and three patients had renal failure. Conclusions: Hypertensive disease in pregnancy requires proper antenatal care, early recognition and referral, adequate treatment and timely delivery.